Impact of artificial intelligence on special needs education - Quinaluisa-Narváez, Katherine Belén; Estévez-Marín, Carlos Esteban (Journal of Asian Scientific Research, 2025)
This study examines the role of Artificial Intelligence (AI) in the education of students with special educational needs (SEN) through a systematic literature review (SLR) and bibliometric analysis of 120 studies published between 2015 and 2025, following the PRISMA protocol. It explores technological advancements, pedagogical applications, thematic trends, and ethical challenges. AI applications, including machine learning, natural language processing, and adaptive systems, demonstrate significant potential for personalizing learning, enhancing accessibility, and supporting the emotional development of students with SEN. However, implementation faces limitations related to teacher training, digital divides, and inadequate regulatory frameworks. Bibliometric analysis revealed sustained growth in publications since 2021, with influential journals such as Educational Technology and Society and the Journal of Special Education Technology standing out. Key research lines include digital accessibility, emotional recognition, personalized learning, and the use of chatbots or smart sensors. Despite progress, a disconnect persists between technological development and effective classroom application, alongside limited representation of studies from the Global South. The study concludes that AI can be a powerful ally for educational inclusion, provided its implementation is guided by ethical principles, inclusive frameworks, and contextual sensitivity. It recommends promoting longitudinal and intersectional research to assess the real impact of these technologies and foster truly equitable education grounded in educational justice.